2003
DOI: 10.1097/01.asn.0000090746.88608.94
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Arteriovenous Grafts in the Thigh and Upper Extremities in Hemodialysis Patients

Abstract: ABSTRACT. Placement of a thigh graft is an option in hemodialysis patients who have exhausted all upper extremity sites for permanent vascular access. The outcome of thigh grafts has been reported only in retrospective studies. The outcomes of 409 grafts placed at a single institution during a 3.5-yr period were evaluated prospectively, including 63 thigh grafts (15% of the total). Information was recorded on surgical complications, dates of radiologic and surgical interventions, and date of graft failure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 25 publications
4
114
3
Order By: Relevance
“…Compared with arm grafts, thigh grafts had a lower thrombosis rate (1.457 versus 0.543/patient-year) and required fewer total PTAs (1.977 versus 0.881/patient-year) to maintain patency (Table 2). These rates are similar to those reported in the literature (10,11). We speculate that the larger diameter of arteries and veins in the thigh may play a role in the lower thrombosis rate observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared with arm grafts, thigh grafts had a lower thrombosis rate (1.457 versus 0.543/patient-year) and required fewer total PTAs (1.977 versus 0.881/patient-year) to maintain patency (Table 2). These rates are similar to those reported in the literature (10,11). We speculate that the larger diameter of arteries and veins in the thigh may play a role in the lower thrombosis rate observed.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Miller et al (10) found that arm and thigh grafts had similar median cumulative survival (22.5 versus 27.6 months) in their prospective study. It is possible that the shorter follow-up of some of these studies may have caused underestimation of thigh graft survival.…”
Section: Discussionmentioning
confidence: 96%
“…We queried the access database retrospectively to identify all thigh arteriovenous grafts placed between January 1, 2003, and June 30, 2011. There was no overlap between the thigh grafts included in this study and those reported previously from our medical center (5). A total of 255 thigh grafts were placed during the 8.5-year study period, for a mean frequency of approximately 30 grafts annually.…”
Section: Discussionmentioning
confidence: 95%
“…All grafts are prone to recurrent stenosis and thrombosis, which can lead to permanent access failure (2), but there are few publications on the outcomes and complication of thigh grafts. Most published studies reported the outcomes of relatively few thigh grafts, with inconsistent definitions of graft outcomes (3)(4)(5)(6)(7)(8)(9)(10)(11). Three larger series (.100 thigh grafts) (12)(13)(14) provided information about graft outcomes using standardized definitions (15) but did not comprehensively analyze clinical factors or comorbid conditions that are associated with thigh graft outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the TCC reference group had the advantage that all TCCs were placed in the internal jugular vein location and the censoring event rate was quite high due to transition to other forms of permanent access. One should also appreciate that an AVG in the upper thigh differs from an upper extremity graft having a higher rate of infections but with similar cumulative patency (11). With these caveats, the results showed that thigh AVGs performed better in terms of patency and infection-free survival then TCCs.…”
mentioning
confidence: 97%